The Effect of Work Shift on Mental Workload of Maintenance Operator Using Nasa Task Load Index (TLX) - Ayu Wirani; Octoberry Julyanto; Dwi Kartini; Mukhlasin Mukhlasin (AGUSPATI Research Institute, 2022)
The workload of workers affects the performance of these workers. Workers are faced with tasks that must be completed at a certain time. Factors that affect a person experiencing a workload are divided into two factors, namely external factors in the form of work station conditions, form of work, and length of time working as well as internal factors in the form of workers' health conditions and psychological conditions of workers. This study discusses the effect of work shifts on the workload of maintenance operators. Information about the workload on the work shifts to the operator can be known based on the subjective workload measurement using the NASA-TLX method as a psychological load measurement. The operator's workload information serves to determine whether the work carried out is in accordance with the workers' abilities so that they can work optimally. The results showed that the mental load conditions of all maintenance operators were included in the high level mental workload with an average score of 62.08 workload on shift I and 69.02 shift II. The calculation results obtained that FCount (3.7)< FTable (4.414), then H0 is accepted, meaning that the work shift has an effect on the Operator's Mental Burden. In addition, the results of the calculation show that FCount (3.698) < FTable (4.414), then H0 is accepted, and it means that the average workload in shift I and Shift II is not significantly different.